Exploring the volatile metabolites of three Chorisia species: Comparative headspace GC-MS, multivariate chemometrics, chemotaxonomic significance, and anti-SARS-CoV-2 potential - John Refaat Fahim; Ahmed G. Darwish; Amr El Zawily; Jacob Wells; Mohammed A.S. Abourehab; Samar Yehia Desoukey; Eman Zekry Attia (Elsevier, 2023)
Chorisia (syn. Ceiba) species are important ornamental, economic, and medicinal plants that are endowed with a diversity of secondary metabolites; however, their volatile organic compounds (VOCs) have been scarcely studied. Therefore, this work explores and compares the headspace floral volatiles of three common Chorisia species, namely Chorisia chodatii Hassl., Chorisia speciosa A. St.-Hil, and Chorisia insignis H.B.K. for the first time. A total of 112 VOCs of varied biosynthetic origins were identified at different qualitative and quantitative ratios, encompassing isoprenoids, fatty acid derivatives, phenylpropanoids, and others. Flowers of the investigated species showed perceptibly differentiated volatile profiles, with those emitted by C. insignis being dominated by non-oxygenated compounds (56.69 %), whereas oxygenated derivatives prevailed among the volatiles of C. chodatii (66.04 %) and C. speciosa (71.53 %). The variable importance in the projection (VIP) in the partial least-squares-discriminant (PLS-DA) analysis described 25 key compounds among the studied species, of which linalool was verified as the most important aroma compound based on VIP values and significance analysis, and it could represent the most typical VOC among these Chorisia species. Furthermore, molecular docking and dynamics analyses of both the major and the key VOCs displayed their moderate to promising binding interactions with four main proteins of SARS-CoV-2, including Mpro, PLpro, RdRp, and spike S1 subunit RBD. The current results collectively cast new light on the chemical diversity of the VOCs of Chorisia plants as well as their chemotaxonomic and biological relevance.